2019
DOI: 10.1038/s41598-019-39617-0
|View full text |Cite
|
Sign up to set email alerts
|

Corneal remodelling and topography following biological inlay implantation with combined crosslinking in a rabbit model

Abstract: Implantation of biological corneal inlays, derived from small incision lenticule extraction, may be a feasible method for surgical management of refractive and corneal diseases. However, the refractive outcome is dependent on stromal remodelling of both the inlay and recipient stroma. This study aimed to investigate the refractive changes and tissue responses following implantation of 2.5-mm biological inlays with or without corneal collagen crosslinking (CXL) in a rabbit model. Prior to implantation, rotation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…Second, the question remains whether CXL is required and whether the CXL should be performed in the lenticule only or the entire cornea. In our study using a rabbit model, we showed that CXL of lenticules limited the flexibility of the lenticular stroma to natural tissue remodeling of the recipient corneas, which in turn, stabilized the refractive status of the corneas earlier and reduced the refractive regression over time [32]. This suggested that CXL is beneficial for the efficacy of the femtosecond laser-assisted keratophakia to prevent loss of effect from stromal remodeling and also endogenous tissue proteases.…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…Second, the question remains whether CXL is required and whether the CXL should be performed in the lenticule only or the entire cornea. In our study using a rabbit model, we showed that CXL of lenticules limited the flexibility of the lenticular stroma to natural tissue remodeling of the recipient corneas, which in turn, stabilized the refractive status of the corneas earlier and reduced the refractive regression over time [32]. This suggested that CXL is beneficial for the efficacy of the femtosecond laser-assisted keratophakia to prevent loss of effect from stromal remodeling and also endogenous tissue proteases.…”
Section: Discussionmentioning
confidence: 63%
“…However, the risk of persistent haze development induced by CXL in patients, typically with advanced keratoconus, has to be considered if one decides to cross-link the entire cornea [52]. Our model was one of presbyopic treatment [32], but when used in a keratoconic patient, the recipient cornea is also biomechanically weaker, hence, it would be advantageous to cross-link the complete cornea with the lenticule implanted. Third, the implantation depth plays a role in determining the refractive effects of the lenticule implantation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, Yin et al studied a method for reconstruction and thickening of lenticules to meet clinical requirements (Yin et al, 2016). Damgaard et al suggested that prior corneal crosslinking (CXL) induction of SMILE-derived lenticules may reduce time to refractive stabilization, but it also requires longer postoperative steroid treatment (Damgaard et al, 2019). However, additional research is needed to confirm if the additional CXL step reduces the incidence of iatrogenic keratectasia (Lau et al, 2019).…”
Section: Corneal Stromal Lenticule Transplantationmentioning
confidence: 99%
“…Another option for detecting ultrastructure in the cornea is histology, which requires the anatomy of the tissue and therefore only applicable for ex vivo tissue. Some other methodologies including X‐ray microscopy and confocal microscopy also have various limitations, such as harmfulness from radiation damage, small imaging area or shallow imaging depth, causing difficulties in clinical eye diagnostics.…”
Section: Introductionmentioning
confidence: 99%